2011
DOI: 10.1002/cssc.201100261
|View full text |Cite
|
Sign up to set email alerts
|

Biobutanol Separation with the Metal–Organic Framework ZIF‐8

Abstract: Keep ′em separated: Bioalcohols are alternatives to petroleum‐based chemicals. Particularly biobutanol is an interesting compound, with properties superior to bioethanol. It is difficult, however, to separate biobutanol from the mixtures produced by the fermentation of biomass. This Communication describes a zeolitic imidazolate framework suitable for the separation of biobutanol from fermentation broths by adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 38 publications
16
99
0
Order By: Relevance
“…At the respective threshold pressures, pronounced optical shifts of about 50-60 nm are recorded, which gradually increase up to saturation pressure. The S-shaped isotherms upon methanol and ethanol adsorption recorded for both the single ZIF-8 films and for BS-2 are in good agreement with the results obtained by Remi et al 44 The authors attribute the S-shaped isotherms to changes in the framework triggered by interactions with guest-molecules, which was additionally confirmed and described elsewhere. 42 In contrast to the distinct S-shaped isotherms, isobutanol sorption experiments yield an almost linearly increasing adsorption behavior with an absolute shift of about 100 nm at the highest partial pressure.…”
Section: 32supporting
confidence: 79%
“…At the respective threshold pressures, pronounced optical shifts of about 50-60 nm are recorded, which gradually increase up to saturation pressure. The S-shaped isotherms upon methanol and ethanol adsorption recorded for both the single ZIF-8 films and for BS-2 are in good agreement with the results obtained by Remi et al 44 The authors attribute the S-shaped isotherms to changes in the framework triggered by interactions with guest-molecules, which was additionally confirmed and described elsewhere. 42 In contrast to the distinct S-shaped isotherms, isobutanol sorption experiments yield an almost linearly increasing adsorption behavior with an absolute shift of about 100 nm at the highest partial pressure.…”
Section: 32supporting
confidence: 79%
“…A large number of strategies have been studied, but for application, drug-delivery systems must overcome issues surrounding bioavailability,7, 8 the uncontrollable release of drugs (usually due to carrier instability),9, 10, 11 loading capacities,11, 12, 13 particle size,14, 15, 16 nanoparticle cellular internalization routes,14, 17, 18 and toxicity 19, 20. The exceptional storage capacities of metal-organic frameworks (MOFs), together with their robustness and structural tailorability, have made them attractive for a wide variety of applications,21, 22 including several promising breakthroughs in biomedicine 9, 10, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. One of their main advantages is that their cytotoxicity and properties can be tuned by the thoughtful choice of metal and linkers 20, 34, 35…”
Section: Introductionmentioning
confidence: 99%
“…As a typical MOF, ZIF‐8 has been well investigated for the adsorption of alcohols in the form of bulk powders as well as thin films . It was found that at high relative pressure the adsorption decreases as the linear alkyl group of the alcohols extends due to limited pore apertures.…”
Section: Resultsmentioning
confidence: 72%